2019
DOI: 10.3390/pharmaceutics11040179
|View full text |Cite
|
Sign up to set email alerts
|

Biodistribution and Physiologically-Based Pharmacokinetic Modeling of Gold Nanoparticles in Mice with Interspecies Extrapolation

Abstract: Gold nanoparticles (AuNPs) are a focus of growing medical research applications due to their unique chemical, electrical and optical properties. Because of uncertain toxicity, “green” synthesis methods are emerging, using plant extracts to improve biological and environmental compatibility. Here we explore the biodistribution of green AuNPs in mice and prepare a physiologically-based pharmacokinetic (PBPK) model to guide interspecies extrapolation. Monodisperse AuNPs were synthesized and capped with epigalloca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 46 publications
(72 reference statements)
4
42
0
Order By: Relevance
“…Furthermore, the base model for large molecules and therapeutic proteins in PK‐Sim does not explicitly include a hematopoietic cell compartment in addition to a vascular endothelial cell compartment, such as in the models put forward by Li and Balthasar or Aborig et al . Instead, the impacts of cellular uptake by vascular endothelial cells and hematopoietic cells are lumped together into 1 endosomal compartment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the base model for large molecules and therapeutic proteins in PK‐Sim does not explicitly include a hematopoietic cell compartment in addition to a vascular endothelial cell compartment, such as in the models put forward by Li and Balthasar or Aborig et al . Instead, the impacts of cellular uptake by vascular endothelial cells and hematopoietic cells are lumped together into 1 endosomal compartment.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, the impacts of cellular uptake by vascular endothelial cells and hematopoietic cells are lumped together into 1 endosomal compartment. To correctly account for the ontogeny of this cell population, we have split the relative contributions to cellular uptake equally between vascular endothelium and hematopoietic cells in the absence of specific data, though this fraction may vary among specific organs (eg, spleen, where macrophages make up 30% of the cell content).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different pharmacokinetic models such as compartmental and especially physiologically based pharmacokinetic (PBPK) models have been developed to characterize the disposition of drugs in different organs and tissues, and especially in the liver, when they are administered in different types of nanoparticles (98,(106)(107)(108)(109)(110)(111)(112).…”
Section: Pharmacokinetic Modelsmentioning
confidence: 99%
“…However, AuNP can exhibit a cytotoxic profile, when the size of the nanoparticles is below 2 nm (ultrasmall AuNP) or when the stabilizing ligands determine a direct interaction with biomolecules or for catalytic activity of the unshielded gold surface. It has been reported that these ultrasmall AuNPs exhibit significantly different biodistribution and enhanced circulation times compared to larger AuNPs [81][82][83][84][85].…”
Section: Biodistribution and Toxicity Aspects Of Gold Nanoparticlesmentioning
confidence: 99%